2019
DOI: 10.1016/j.conbuildmat.2019.06.113
|View full text |Cite
|
Sign up to set email alerts
|

Inductive method for the orientation of steel fibers in recycled mortars

Abstract: It's possible the complete substitution of natural by recycled aggregates in mortars.• Addition of orientated fibers improves the mechanical properties of cement mortars. • A magnetic system has been developed to orientate steel fibers in cement mortars. • It's possible to qualify magnetically the quantity of fibers orientates in mortars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…In this work, synthetic fibers of plastic origin were used as reinforcement material in mortars made with recycled aggregate, with the aim of increasing its durability, improving its mechanical resistance and reducing its retraction [49]. The fibers were supplied by SIKA (Madrid, Spain).…”
Section: Fibersmentioning
confidence: 99%
“…In this work, synthetic fibers of plastic origin were used as reinforcement material in mortars made with recycled aggregate, with the aim of increasing its durability, improving its mechanical resistance and reducing its retraction [49]. The fibers were supplied by SIKA (Madrid, Spain).…”
Section: Fibersmentioning
confidence: 99%
“…According to previous studies, mechanical properties of fresh concrete could be increased by direct applying of a magnetic field [33][34][35][36][37][38][39][40]. In an study by Soto-Bernal et al [33], it is reported that the compressive strength of cement pastes exposed to weak magnetic fields enhanced up to 13%.…”
Section: Introductionmentioning
confidence: 93%
“…It is also shown that the magnetizing technique can control the orientation of fibers in the intended direction and make an orthotropic concrete. Following this, the effect of magnetic field on bending capacity of recycled mortar containing steel fibers was conducted by Ferrandez et al [35]. The results indicated that the magnetic field could increase the bending capacity of mortar by 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, researchers have attempted to use a magnetic field to align the direction of steel fibers mixed in concrete and mortar [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. This method corresponds to the most active research attempt to artificially align the direction of steel fibers in concrete.…”
Section: Introductionmentioning
confidence: 99%